Pengaruh Populasi Tanaman terhadap Pertumbuhan dan Hasil Beberapa Varietas Jagung (Zea mays L.) Lokal di Lahan Kering - Eduardus Yosef Neonbeni; I Gusti Ayu Mas Sri Agung; I Made Suarna (Savana Cendana, 2019)
The decrease of maize yields on dryland farming areas could have resulted from the effects of strong competition between plants in a population due to an inappropriate number of plants, corn variety, and limited growth factors. The use of the right number of plants hole-1 and variety is expected to increase corn seed yield. The results showed that in the population 285,714 plants ha-1, the yield of seeds weighing 7.78 g cob-1 at 12% moisture content and 7.73 ton ha-1 at oven-dry weight, produced by local varieties of the hill. This result indicates that the two factor of treatment did not have an effect on maize yield. The population treatment of 285,714 plants ha-1 yielding seeds weighing 135.23 g plant-1 dry weight oven and 7.73 ton ha-1 on oven dry weight. The local varieties of Bukit produced seeds weighing 90.20 g plant-1 at 12% and 5.13 t ha-1 moisture content on oven dry weight, potentially developed in dryland especially in Mumbul Park area, South Kuta in a population of 285,714 plant ha-1 (4 plants per hole).